Differences in lower extremity alignment between males and females. Potential predisposing factors for knee injury - Tillman, M. D.; Bauer, J. A.; Cauraugh, J. H.; Trimble, M. H. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The goal of this study was to compare measures of lower extremity alignment between males and females, which may account for gender differences in anterior cruciate ligament injury rates. Static lower extremity alignment has been implicated as predisposing individuals to anterior cruciate ligament injury and may vary between males and females. An initial step in identifying relevant risk factors for injury is to determine those factors that vary between genders. Methods: Thirty male and 27 female college aged individuals with no history of lower extremity injury participated. Three indices of lower extremity alignment were measured on each subject: quadriceps angle, thigh foot angle, and subtalar joint range of motion ratio. Results: Q-angles in females exceeded values for males by 4.4° (p<0.001). Thigh foot angle for females was 3.6° greater than for males (p=0.020). Subtalar joint movement ratio did not vary between genders (p=0.573). Conclusion: Previous research suggests that abnormal alignment may predispose individuals to anterior cruciate ligament injury. The present findings may help to explain the difference in anterior cruciate ligament injury rates between males and females. Any tangible links between lower extremity alignment and anterior cruciate ligament injury rates must be confirmed with prospective studies.